Effects of community based nurses specialising in Parkinson's disease on health outcome and costs: randomised controlled trial. Issue 7345 (4th May 2002) - Jarman, Brian; Hurwitz, Brian; Cook, Adrian; Bajekal, Madhavi; Lee, Alison
Abstract: Objective: To determine the effects of community based nurses specialising in Parkinson's disease on health outcomes and healthcare costs. Design: Two year randomised controlled trial. Setting: 438 general practices in nine randomly selected health authority areas of England. Participants: 1859 patients with Parkinson's disease identified by the participating general practices. Main outcome measures: Survival, stand-up test, dot in square test, bone fracture, global health question, PDQ-39, Euroqol, and healthcare costs. Results: After two years 315 (17.3%) patients had died, although mortality did not differ between those who were attended by nurse specialists and those receiving standard care from their general practitioner (hazard ratio for nurse group v control group 0.91, 95% confidence interval 0.73 to 1.13). No significant differences were found between the two groups for the stand-up test (odds ratio 1.15, 0.93 to 1.42) and dot in square score (difference 0.7, 3.25 to 1.84). Scores on the global health question were significantly better in patients attended by nurse specialists than in controls (difference 0.23, 0.4 to 0.06), but no difference was observed in the results of the PDQ-39 or Euroqol questionnaires. Direct costs for patient health care increased by an average of £2658 during the study, although not differentially between groups: the average increase was £266 lower among patients attended by a nurse specialist ( £981 to £449). Conclusions: Nurse specialists in Parkinson's disease had little effect on the clinical condition of patients, but they did improve their patients' sense of wellbeing, with no increase in patients' healthcare costs.